2020
DOI: 10.1177/0898010120903167
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine: A Qualitative Study for Reconsidering Nursing Care in the United States

Abstract: Purpose: Traditional Chinese medicine (TCM) proposes the world as a holistic unity of energy. With a long history of use, TCM is generally accepted in the Chinese health care system. Despite growing global interest and use, TCM has received a mixed response from Western health care systems. This study aimed to describe the underpinnings of TCM, compare TCM and Western medicine, and suggest how key modalities might be applied to strengthen holistic nursing care in the United States. Design: A qualitative, descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“… 66 , 67 Studies have shown that 42% of Americans have experienced CAM methods, a large portion of which are TCM nursing techniques, thus indicating high potential applicability and acceptability internationally. 68 In addition, existing research has indicated that TCM nursing effectively alleviates CRF, and combinations of treatment methods can effectively alleviate the clinical symptoms in oncology patients. 69 Considering the wealth of local evidence resources available, it is crucial to incorporate pertinent TCM nursing evidence beyond the confines of language.…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 67 Studies have shown that 42% of Americans have experienced CAM methods, a large portion of which are TCM nursing techniques, thus indicating high potential applicability and acceptability internationally. 68 In addition, existing research has indicated that TCM nursing effectively alleviates CRF, and combinations of treatment methods can effectively alleviate the clinical symptoms in oncology patients. 69 Considering the wealth of local evidence resources available, it is crucial to incorporate pertinent TCM nursing evidence beyond the confines of language.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is a medical system with a long history and unique theories and techniques [ 8 , 9 ]. In recent years, the use of Chinese herbal medicine treatment of diseases associated with melasma has attracted wide attention.…”
Section: Introductionmentioning
confidence: 99%